2010
DOI: 10.1007/s00018-010-0442-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction between TRPC1 channel and connexin-43 protein: a novel pathway underlying S1P action on skeletal myogenesis

Abstract: We recently demonstrated that skeletal muscle differentiation induced by sphingosine 1-phosphate (S1P) requires gap junctions and transient receptor potential canonical 1 (TRPC1) channels. Here, we searched for the signaling pathway linking the channel activity with Cx43 expression/function, investigating the involvement of the Ca 2? -sensitive protease, m-calpain, and its targets in S1P-induced C2C12 myoblast differentiation. Gene silencing and pharmacological inhibition of TRPC1 significantly reduced Cx43 up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…Similarly, S1P has also been proposed to play an important role in trafficking of non-malignant cells such as hematopoietic stem progenitor cells (6, 44), mesenchymal stromal cells (45), and endothelial progenitors (17). It thus plays a role in skeletal muscle development (46), angiogenesis (47), and tissue regeneration from injury (9) and acts directly on skeletal muscle satellite stem cells (26). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, S1P has also been proposed to play an important role in trafficking of non-malignant cells such as hematopoietic stem progenitor cells (6, 44), mesenchymal stromal cells (45), and endothelial progenitors (17). It thus plays a role in skeletal muscle development (46), angiogenesis (47), and tissue regeneration from injury (9) and acts directly on skeletal muscle satellite stem cells (26). …”
Section: Discussionmentioning
confidence: 99%
“…The effects of S1P and C1P in myogenesis (8, 46) could be relevant to the effect on RMS proliferation. However, we did not observe any effect of either bioactive lipid on proliferation or survival of RMS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesions act as multi-protein signaling complexes as well as having the structural role of linking membrane receptors and the actin cytoskeleton. Gap junctions are an important component of intercalated discs in cardiac muscle [43] and are necessary for skeletal muscle differentiation [44]. Tight junctions, also known as zonula occludens, are important for signaling [45].…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways leading to TRPC activation is still a debated issue, but it was shown that TRPC1, TRPC4 and TRPC5 participate to SOCE in several cell types (Ambudkar, 2007;Worley et al, 2007;Yuan et al, 2007;Salido et al, 2011), including primary mouse myotubes and C2C12 mouse muscle cell line (Vandebrouck et al, 2007;Louis et al, 2008;Sabourin et al, 2009). In addition, TRPC1 was shown to play an important role to sustain skeletal muscle contraction (Zanou et al, 2010) and, in C2C12 cell line, TRPC1 silencing decreased SOCE and the fusion process (Louis et al, 2008;Formigli et al, 2009;Meacci et al, 2010), hence impairing muscle formation. Another study reported a role of TRPC3 in myogenesis, but using cells that also lack the dihydropyridine receptor (Woo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%